Szegő projections for hardy spaces of monogenic functions and applications - Swanhild Bernstein; Loredana Lanzani (International Journal of Mathematics and Mathematical Sciences)
We introduce Szegő projections for Hardy spaces of monogenic functions defined on a bounded domain Ω in ℝn. We use such projections to obtain explicit orthogonal decompositions for L2(bΩ). As an application, we obtain an explicit representation of the solution of the Dirichlet problem for balls and half spaces with L2, Clifford algebra-valued, boundary datum.